Association between Body Composition and Peripheral Neurotoxicity in Cancer Patients from North China Taking Nab-Paclitaxel. (16th March 2023) - Guo, Jiayuan; Zhao, Juan; Gu, Ming; Hou, Jixiang; Xu, Ting; Jiang, Ying; Jiang, Caihong; Li, Hui; Li, Xiaorong; Liu, Guang; Zhao, Lanzhen; Jin, Gaowa; et al.
Abstract: Determine the association of lean body mass (LBM) on the incidence and severity of peripheral neurotoxicity in cancer patients who received nab-paclitaxel alone or combined with cisplatin or carboplatin. This prospective clinical study examined 32 cancer patients classified into a sarcopenia or non-sarcopenia group according to the Asian L3 vertebra skeletal muscle index (L3-SMI) at Ordos Central Hospital (China) from December 2020–2021, to compare the incidence and severity of neurotoxicity and analizing the relationship between nab-paclitaxel dose per kg LBM and neurotoxicity. There were 18 patients (56.25%) in the sarcopenia group and 14 (43.75%) in the non-sarcopenia group. The incidences of peripheral and severe neurotoxicity were higher in the sarcopenia group (both P < 0.05). Patients in three different body surface area (BSA) groups received the same nab-paclitaxel dose (260 mg/m 2 BSA). However, when patients were divided into three groups according to LBM, they received different doses (low-LBM: 15.18 mg/kg LBM, middle-LBM: 12.82 mg/kg LBM, and high-LBM: 11.14 mg/kg LBM). The incidence of grade-C or higher neurotoxicity of these three groups was 61.54% (8/13), 20.00% (1/5), and 11.11% (1/9). Sarcopenia and a higher dose of nab-paclitaxel per kg LBM were associated with peripheral and severe neurotoxicity. Chemotherapy dosing based on body composition may reduce neurotoxicity in patients receiving nab-paclitaxel. Registration number of Clinical Trial: ChiCTR2000040918.